Thermoelectric properties of n-type Cu4Sn7S16-based compounds. Issue 14 (8th March 2019) - Deng, Tingting; Wei, Tian-Ran; Song, Qingfeng; Xu, Qing; Ren, Dudi; Qiu, Pengfei; Shi, Xun; Chen, Lidong
Abstract : Thermoelectric properties were optimized by Ag-doping in n-type Cu4 Sn7 S16 -based compounds with complex structure, small effective mass and low thermal conductivity. Abstract : Copper-based chalcogenides have ultralow thermal conductivity and ultrahigh thermoelectric performance, but most of them are p-type semiconductors. It is urgent to develop n-type counterparts for high efficiency thermoelectric modules based on these copper based-chalcogenides. Cu4 Sn7 S16 is an intrinsically n-type semiconductor with complex crystal structure and low thermal conductivity. However, its thermoelectric properties have not been well studied when compared to the well-known n-type CuFeS2 . In this work, high-quality Cu4 Sn7 S16 -based compounds are fabricated and their thermoelectric properties are systematically studied. Using Ag and Sb as dopants, the carrier concentration is tuned over a wide range. The electrical transport properties can be well described by the single parabolic band model with carrier acoustic phonons scattering. It is revealed that Cu4 Sn7 S16 exhibits a low effective mass and relatively high mobility. The thermal conductivity is lower than 0.8 W m −1 K −1 from 300 to 700 K and shows a weak dependence on temperature. A maximum zT of 0.27 is obtained in Cu3.97 Ag0.03 Sn7 S16 at 700 K. Further enhancement of thermoelectric performance is possible when a more efficient n-type dopant is used.